Predicting Corporate Financial Failure Using the Zmijewski Model Case Study of Companies Listed on the Algerian Stock Exchange for the Period (2020-2024) - slimani, abdelhakim (Journal of Research in Finance and Accounting, 2025)
This study aims to highlight the ability and contribution of the Zmijewski model in revealing the financial situation of listed companies and predicting their financial failure. To achieve this, the descriptive method was adopted in the theoretical aspect by reviewing the conceptual framework of the study variables, and the case study method in the applied aspect by applying the Zmijewski model on three companies listed on the Algerian Stock Exchange based on their financial statements for the period (2020-2024). Based on the results of the model, it is clear that Biopharm enjoys strong and stable financial indicators that make it far from the risk of financial failure, while Alliance Insurance Company, despite its presence in the safe zone, its financial situation is deteriorating and approaching the risk zone and therefore it is in urgent need to take corrective measures to prevent the continuation of this deterioration in the future, and the Eurasian Hotel Management Company, despite its approach to the risk of financial failure during the first two years, is in an urgent need to take corrective measures to prevent the continuation of this deterioration. The Eurasian Hotel Management Company, despite approaching the threshold of the risk of financial failure during the first two years, its financial performance is continuously improving to strengthen its position within the safe zone, and it is required to continue monitoring and improving its financial situation to ensure future stability and avoid moving into the risk zone.